Analisis Kelayakan Usaha dan Strategi Pengembangan Tanaman Talas Beneng (Xanthosoma undipes K.Kock) dalam Meningkatkan Pendapatan Petani - Auli, Wildan; Karyani, Tuti (Universitas Galuh, 2024)
ABSTRACT The agricultural sector plays a very important role in ensuring the most basic needs of society, namely the availability of food as a basic need. Apart from rice, food crop commodities that can be an alternative for fulfilling national food are taro, one of which is beneng taro. Apart from good nutrition, the potential of beneng taro is that it is easy to cultivate and has high economic value because all parts of the plant can be used, from the leaves to the tubers. This research aims to find out how much income farmers receive and whether beneng taro farming is worth pursuing and what the strategy for developing beneng taro is. The research method uses a case study method with respondents who are beneng taro farmers. The research was conducted in Jatiwaras District, Tasikmalaya Regency. The data used consists of primary and secondary data. Data analysis uses R/C, B/C analysis, and SWOT analysis. The research results show that beneng taro farming is worth pursuing with an SO development strategy, namely maximizing the cultivation process, establishing collaboration with various agencies and institutions, and developing products with SME.